Performance of Polyester-Based Electrospun Scaffolds under In Vitro Hydrolytic Conditions: From Short-Term to Long-Term Applications - Gil-Castell, Oscar (Nanomaterials (Basel), 2019)
The evaluation of the performance of polyesters under in vitro physiologic conditions is essential to design scaffolds with an adequate lifespan for a given application. In this line, the degradation-durability patterns of poly(lactide-co-glycolide) (PLGA), polydioxanone (PDO), polycaprolactone (PCL) and polyhydroxybutyrate (PHB) scaffolds were monitored and compared giving, as a result, a basis for the specific design of scaffolds from short-term to long-term applications. For this purpose, they were immersed in ultra-pure water and phosphate buffer solution (PBS) at 37 °C. The scaffolds for short-time applications were PLGA and PDO, in which the molar mass diminished down to 20% in a 20–30 days lifespan. While PDO developed crystallinity that prevented the geometry of the fibres, those of PLGA coalesced and collapsed. The scaffolds for long-term applications were PCL and PHB, in which the molar mass followed a progressive decrease, reaching values of 10% for PCL and almost 50% for PHB after 650 days of immersion. This resistant pattern was mainly ascribed to the stability of the crystalline domains of the fibres, in which the diameters remained almost unaffected. From the perspective of an adequate balance between the durability and degradation, this study may serve technologists as a reference point to design polyester-based scaffolds for biomedical applications.